2020
DOI: 10.1002/lio2.353
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in laryngeal squamous cell carcinoma

Abstract: Background The current treatment results of laryngeal squamous cell carcinoma still remain modest. Various prognostic factors have been investigated and need to be included in the management decision making. Methods We reviewed the pertinent literature regarding host, tumor, and treatment factors as prognostic indicators that influence outcome in patients diagnosed with laryngeal squamous cell carcinoma. Results Host, tumor, and treatment factors all have an important impact upon an individual patient's progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 73 publications
3
58
0
1
Order By: Relevance
“…In the present study, multivariate analysis ( Tab. III ) confirmed that only a pathological finding of neck metastasis was an independent negative prognostic factor in terms of recurrence rate (p = 0.05), consistent with the current literature on laryngeal cancer 26 . On the other hand, the impaired arytenoid motility, CAU invasion and need for OPHL type III were not independent negative prognostic factors.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, multivariate analysis ( Tab. III ) confirmed that only a pathological finding of neck metastasis was an independent negative prognostic factor in terms of recurrence rate (p = 0.05), consistent with the current literature on laryngeal cancer 26 . On the other hand, the impaired arytenoid motility, CAU invasion and need for OPHL type III were not independent negative prognostic factors.…”
Section: Discussionsupporting
confidence: 88%
“…It includes a heterogenous group of patients with different outcomes, so more appropriate treatment modalities tailored to each case on its own should be offered. This necessitates patient stratification based on other prognostic factors to be added to the traditional, limited WHO grading system [ 3 , 13 ]. Tumor budding is a microscopic finding detected by light microscopy at the invasive front of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning lymph node metastases, although the number, size and level of the invaded lymph nodes were considered important, yet extracapsular spread proved to be of exceedingly paramount prognostic importance [ 13 , 24 ]. Our current study showed a high statistical significance between tumor budding and extracapsular spread which highlights the probable prognostic value of tumor budding in laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown the importance of several prognostic factors as predictors for organ preservation, treatment response, and outcomes in laryngeal cancer patients [ 55 , 56 , 57 ]. An area of interest is the pretreatment larynx function and his predictor value for response to RT or chemoradiation.…”
Section: Locally Advanced Stage (Iii–iv)mentioning
confidence: 99%